2018
DOI: 10.1016/j.carbpol.2018.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(ethylene terephthalate) films coated by chitosan and vermiculite nanoclay

Abstract: Chitosan (CS) layers are coated on a poly(ethylene terephthalate) (PET) film in order to decrease the oxygen permeability through the polymeric films for food packaging applications. Oxygen transmission rate (OTR) of the 130 μm PET films can be decreased from 11 to only 0.31 cm/m².day with a coated layer of 2 μm of CS. Additional decrease is obtained with the addition of vermiculite (VMT) to CS matrix in high proportion (40 to 50 w/w%). The OTR of the coated PET films decreased to very low values, below the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Composites can be evaluated as intercalated or exfoliated composites and these composites can be fabricated by various methods including melt mixing, in situ polymerization, solution casting, or a combination of solution casting and compression molding. In the literature, various types of thermoplastics including polypropylene, 1822 polyethylene, 2325 poly(l-lactic acid), 26 polylactide, 27 polyamide, 28 polyimide, 29 polyethylene terephthalate, 30 poly(4-vinyl pyridine), 31 polyvinyl alcohol, 32 poly(p-dioxanone) 33 or their blends 34 were used. Epoxy, 35,36 phenol formaldehyde 37 were the most common thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Composites can be evaluated as intercalated or exfoliated composites and these composites can be fabricated by various methods including melt mixing, in situ polymerization, solution casting, or a combination of solution casting and compression molding. In the literature, various types of thermoplastics including polypropylene, 1822 polyethylene, 2325 poly(l-lactic acid), 26 polylactide, 27 polyamide, 28 polyimide, 29 polyethylene terephthalate, 30 poly(4-vinyl pyridine), 31 polyvinyl alcohol, 32 poly(p-dioxanone) 33 or their blends 34 were used. Epoxy, 35,36 phenol formaldehyde 37 were the most common thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…e thermal analysis indicated that significant changes in thermal properties were obtained within the first four months, among the filled PET and control bottle. In other types of PET modification, Essabti et al achieved an OTR reduction of up to 94.87% with two coated layers of 1 wt.% chitosan:40 wt.% vermiculite nanoclay on 130 µm PET film (0.31 cm 3 •m −2 day −1 ) [126].…”
Section: Polyethylene Terephthalate (Pet)mentioning
confidence: 99%
“…The biopolymer nanocomposite coating was found to improve the mechanical properties of the paper packaging material, as well as inhibit microbial growth on the material’s surface [ 152 ]. Biodegradable coatings with chitosan incorporating vermiculite nanoclay on a PET substrate, resulting in a significant decrease in the oxygen permeability, have also been reported [ 153 ].…”
Section: Active Nanocomposite Filmsmentioning
confidence: 99%